The Effect Of Gratitude On Body Image Of Early Adult Women In Medan City - Nababan, Chintya Dewi Ruth; Butar-butar, Freddy (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
This study aims to determine The Effect of Gratitude on Body Image in Early Adult Women in Medan City. Based on the results of research conducted on 301 early adult female respondents aged 18–25 years in Medan City, it shows that H0 is rejected and H1 is accepted, which means there is a positive and significant influence between gratitude on body image, as much as 13.6% of variations in body image can be explained by the level of gratitude, while others are influenced by other factors outside the variables studied. In addition to gratitude, there are other variables or factors that also influence body image, including: Self-esteem (Rifka & Prasetyo, 2019), Social and media pressure (Perloff, 2014), Social comparison (Fardouly et al., 2015), Social support (Tiggemann & Slater, 2004) and Interpersonal Experience (Cash & Pruzinsky, 2002). The majority of respondents in this study had a high level of gratitude (74.4%), reflecting their ability to respond positively to life experiences, including their own physical condition. Individuals with high levels of gratitude tend to be more accepting of themselves as a whole, view their bodies as a gift, and are less affected by social pressures regarding physical appearance. These findings support the theory of Emmons & McCullough (2003), which states that gratitude is a form of positive emotion that can improve psychological well-being and self-acceptance, including physical aspects.